Incidence of Symptomatic Pulmonary Embolus and Deep Vein Thrombosis After Knee Arthroscopy in the Pediatric and Adolescent Population. Issue 4 (July 2019) - Lau, Brian C.; Jagodzinski, Jason; Pandya, Nirav K.
Abstract : Objective: The incidence of deep venous thrombosis (DVT) and pulmonary embolism (PE) after pediatric knee arthroscopy is unknown. The purpose of this study was to determine the incidence of venous thromboembolism (VTE) after knee arthroscopy in the pediatric and adolescent population in a high-volume center. Design: Retrospective cohort study. Setting: Tertiary care children's hospital. Patients: All patients who underwent arthroscopy of the knee for a sports-related injury by 2 surgeons were reviewed. Chief complaint, past medical/surgical history, medications, procedure performed, intraoperative findings, intraoperative complications, and postoperative recovery were reviewed. The incidences of postoperative VTE within 30 days after the procedure were reviewed. Results: Seven hundred forty-six (358 male and 388 female patients) knee arthroscopies performed from September 2011 to October 2016 by 2 pediatric orthopedic surgeons specializing in sports-related injuries were included. The average age was 15.2 ± 2.72 years. Five patients were suspected to have either DVT or PE postoperatively (0.67%). The overall incidence of symptomatic confirmed VTE after knee arthroscopic procedures was 0.27% (one DVT after a partial lateral meniscectomy and one PE after fixation of an osteochondral lesion). Conclusions: The incidence of VTE after pediatric sports medicine knee arthroscopies is low, 0.27%. Patients who present with calf swelling or pain, chest pain, or shortness of breath after arthroscopic surgery should be examined closely. Level of Evidence: Level III.